Lysine catabolism, amino acid transport, and systemic acquired resistance: What is the link? - Yang, Huaiyu (Landes Bioscience, 2014)
Lysine is an essential amino acid for human nutrition, which is generally low in cereal diets. Its biosynthesis via the aspartate-pathway and catabolism is controlled by complex feedback mechanisms. Recently, aspartate-derived amino acids were found to be elevated during pathogen infection in Arabidopsis and a lysine catabolite, pipecolic acid, was identified as critical regulator of systemic acquired resistance. Pipecolic acid is mobile in plants, functions as an intensifier of defense responses and mediates systemic acquired resistance establishment via signal amplification. The altered pathogen defense in several mutants with altered homeostasis of aspartate-derived amino acids, such as lysine, had already provided a genetic link with amino acid homeostasis. Furthermore, the modification of amino acid transport and distribution within tissues not only affected the plant growth performance, but also the plant-pathogen interaction. The ectopic overexpression of a gene encoding a high affinity importer with preference to basic amino acids, such as lysine, CATIONIC AMINO ACID TRANSPORTER1 (CAT1), improved the disease resistance to a hemibiotrophic bacterial pathogen in Arabidopsis via a constitutively activated salicylic acid pathway. The importance of Asp-derived amino acid homeostasis for plant systemic acquired resistance and on overall plant growth performance may be relevant to resistance and nutritional quality breeding. Whether nitrogen fertilization has an impact on crop pest control management via amino acid homeostasis is briefly discussed.